Peru - Restoring Fiscal Discipline for Poverty Reduction : A Public Expenditure Review - World Bank (Washington, DC, 2013)
This public expenditure review is produced jointly by the World Bank and the Inter-American Development Bank, and focuses on social sectors spending and leaves aside infrastructure and other sectors. This report, finalized in June 2002 and discussed with Authorities in mid-August 2002, does not take into account policy developments occurring after this time. The report is organized as follows: Chapter 1 presents a synthesis of Peru's public expenditure reform agenda from the Bank's perspective. It is based on, and distills, the thematic chapters that make up this report. Chapters 2-4 examine the core functions of public expenditure management: macro fiscal aggregates, resource allocations to strategic sectors, and microeconomic efficiency of public spending. Chapters 5-8 explore selected themes, such as the decentralization of public administration and the social sectors; civil service reform; governance and corruption; and and mining fiscal and environmental issues. These chapters are, in turn, supported by fifteen topic-specific background papers, including an innovative public expenditure tracking survey on municipal transfers. Other topics focus on public sector employment; decentralization of health and education; an empirical diagnostic study on governance, rule of law, and corruption; and a comparison of the Peruvian tax system with mining tax systems in other nations.